THE EFFECTIVENESS OF SELF MANAGEMENT ENGINEERING GROUP COUNSELING TO IMPROVE LEARNING DISCIPLINES FOR CLASS VII STUDENTS OF MTS MUKHTAR INTERFACE BLOKAGUNG EVEN SEMESTER 2020/2021 ACADEMIC YEAR 2020/2021 - Harwanti Noviandari; Meiza Cahya Bayu Dwilianto; Tofan Priananda Adinata (MAN Insan Cendekia Jambi, 2021)
Dwilianto, Meiza Cahya Bayu. 2021; The Effectiveness of Self Management Technique Group Counseling to Improve Student Discipline in Class VII MTs Mukhtar Syafaat Blokagung Even Semester for the 2020/2021 Academic Year.50 pages; Counseling Guidance Study Program, Faculty of Teacher Training and Education, PGRI University Banyuwangi. Advisors: (1) Harwanti Noviandari, S.Psi, M.Psi (II) Tofan Priananda Adinata, M.Si The application of Self Management to students is caused by applying the Self Management students can find out a description of the source of the problems that exist within themselves, so that he himself can complete and eliminate the habits that hinder him in the learning process. The aim of this research is to find out whether self-management techniques are effective in improving the learning discipline of class VII students at MTs Mukhtar Syafaat Blokagung for the 2020/2021 academic year. The formulation of the problem in this study is as follows